The impact of feedback on dietary intake and body composition of college women volleyball players over a competitive season - Anderson, D. E. (The Journal of Strength and Conditioning Research, 2010)
The purpose of this study was to examine the impact of nutritional feedback on dietary intake and body composition of college women volleyball players. Eight members of an National Collegiate Athletic Association (NCAA) division II women's volleyball team participated as subjects. Three-day diet records and body composition (via air displacement plethysmography) were analyzed at the beginning of the season (Beginning), peak training during the season (Peak), and 1 week postseason (After). During the first season (Baseline), the athletes were given no information concerning their dietary intakes. In the following year (Feedback), athletes were given information with regard to dietary intakes of themselves and the team as a whole. Percent body fat was not significantly different between Baseline and Feedback trials. During Beginning and Peak, the mean energy intakes ranged from 35.3 to 40.8 kcal/kg.BW. Protein intake was significantly greater in Feedback-Beginning (1.5 ± 0.9 g/kg·BW) compared to Baseline-Beginning (1.1 ± 0.1 g/kg·BW). No significant differences were seen in Baseline vs. Feedback for either carbohydrate or fat intakes. The only vitamin with significantly different consumption was vitamin C, with intakes of Feedback-Beginning (303.8 ± 99.8% Dietary Reference Intakes [DRI]) vs. Baseline-Beginning (115.3 ± 32.3% DRI). A significantly greater amount of calcium was consumed at Feedback-Beginning (152.0 ± 25.2% DRI) compared to Baseline-Beginning (102.2 ± 21.2% DRI). In conclusion, dietary feedback resulted in increased intake of protein, vitamin C, and calcium at the beginning of the season only for female collegiate volleyball players. Other than an increase in fiber, dietary intake at the peak of the season and postseason was not influenced by feedback. Body composition was unaffected by feedback at Beginning, Peak, and After.